Bias-stress effects in diF-TES-ADT field-effect transistors. (March 2019) - Kim, Chang-Hyun
Highlights: Bias-stress effects in diF-TES-ADT transistors are strongly electrode-dependent. Transfer curves of the devices are assessed by a holistic modeling approach. Contact resistance plays an important role in describing the stress responses. Abstract: A systematic analysis of the bias-stress effects in solution-processed organic field-effect transistors is reported. Difluoro 5, 11-bis(triethylsilylethynyl) anthradithiophene, a high-performance molecular semiconductor, forms a charge-transport channel and is coupled with injection contacts made of Au, Ag, or Cu. The electrode metal is found to not only greatly affect the switching performances but also drive the response of transistors to the extended applications of gate voltage. The observations are put into the framework of contact-limited transistor model, which holistically assesses the material, geometry, and stress-related contributions.